1991
DOI: 10.1136/emj.8.4.253
|View full text |Cite
|
Sign up to set email alerts
|

Inability to fully extend the injured elbow: an indicator of significant injury.

Abstract: SUMMARYElbow injuries are commonly seen in accident departments. Patients with possible bony injuries to the elbow were assessed to see if inability to fully extend the elbow was a good indicator of bony injury and hence the need for X-ray.The sensitivity of this test was 90-7% (95% confidence limits 80-7-100-7) and the specificity 69-5% (95% confidence limits 60.3-78.7). Use of this simple test would reduce both radiography costs and unnecessary exposure to radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 2 publications
1
24
0
1
Order By: Relevance
“…Seventy-six were eliminated based on reference standard, patient type, and study design, leaving seven studies. Two additional studies were identified that fit the inclusion and exclusion criteria after reviewing the references of the prior seven studies, resulting in nine studies (Appelboam et al, 25 Baker and Borland, 26 Cevik et al, 27 Darracq et al, 28 Docherty et al, 29 Hawksworth and Freeland, 30 Lennon et al, 31 Pershad et al, 32 and Webster et al 33 ) that were included in the systematic review of history and physical examination findings that were suggestive of upper extremity fracture.…”
Section: Description Of Included Studies: History and Physicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-six were eliminated based on reference standard, patient type, and study design, leaving seven studies. Two additional studies were identified that fit the inclusion and exclusion criteria after reviewing the references of the prior seven studies, resulting in nine studies (Appelboam et al, 25 Baker and Borland, 26 Cevik et al, 27 Darracq et al, 28 Docherty et al, 29 Hawksworth and Freeland, 30 Lennon et al, 31 Pershad et al, 32 and Webster et al 33 ) that were included in the systematic review of history and physical examination findings that were suggestive of upper extremity fracture.…”
Section: Description Of Included Studies: History and Physicalmentioning
confidence: 99%
“…The sample size ranged from 48 32 to 1,740 patients. 25 Of the nine included trials, six 25,26,[28][29][30][31] studied elbow injuries, and three 27,32,33 studied wrist injuries. Of the elbow studies, five 25,28-31 included both adult and pediatric patients, one 25 of which analyzed the adult and pediatric patients on separate arms.…”
Section: Description Of Included Studies: History and Physicalmentioning
confidence: 99%
“…However, the addition of point tenderness at the olecranon, epicondyles and radial head did not improve the sensitivity or specificity of the active ROM maneuvers in the detection of elbow fractures. [10][11][12] In our study, patients with partial limitation in one or two movements had no sign of fractures on the Xray. However, almost all patients with fracture had limited range in all movements.…”
Section: Discussionmentioning
confidence: 40%
“…In the literature, linear fracture of the head of the radius [1,[10][11][12] and fracture of the olecranon [10][11][12] were two injuries observed in patients with normal ROM. However, the addition of point tenderness at the olecranon, epicondyles and radial head did not improve the sensitivity or specificity of the active ROM maneuvers in the detection of elbow fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation